2001
DOI: 10.1021/bi010010s
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Photoreactive Spermine Analogues on Peptide Bond Formation and Their Application for Labeling Proteins in Escherichia coli Functional Ribosomal Complexes

Abstract: The effect of two photoreactive analogues of spermine, N(1)-azidobenzamidino- (ABA-) spermine and N(1)-azidonitrobenzoyl- (ANB-) spermine, on ribosomal functions was studied in a cell-free system derived from Escherichia coli. In the dark, both analogues stimulated the binding of AcPhe-tRNA to poly(U)-programmed ribosomes, enhanced the stability of the ternary complex AcPhe-tRNA.poly(U).ribosome (complex C), and caused stimulatory and inhibitory effects on peptidyltransferase activity. ABA-spermine exhibited m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
9

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 35 publications
0
16
1
9
Order By: Relevance
“…Previous studies of our group have demonstrated that ABA-spermine retains almost all biochemical properties of the parent compound (29,30). On the other hand, photolabeled complex C with ABA-spermine exhibits similar kinetic properties in peptide-bond formation to those obtained with untreated complex C reacting with spermine free in solution (30). Therefore, it is reasonable to believe that ABA-spermine binds specifically to the ribosome.…”
Section: Polyamines Reduce the Binding Of Spiramycin To Complex C-earmentioning
confidence: 70%
“…Previous studies of our group have demonstrated that ABA-spermine retains almost all biochemical properties of the parent compound (29,30). On the other hand, photolabeled complex C with ABA-spermine exhibits similar kinetic properties in peptide-bond formation to those obtained with untreated complex C reacting with spermine free in solution (30). Therefore, it is reasonable to believe that ABA-spermine binds specifically to the ribosome.…”
Section: Polyamines Reduce the Binding Of Spiramycin To Complex C-earmentioning
confidence: 70%
“…The photoreactive analogue retains a charge in the vicinity of the nearest amino group, closely resembling spermine. This may explain the fact that ABA-spermine in the dark displays similar biological activity to that determined for spermine when used as a component of the ionic environment of ribosomes (27). Photolabeling of ribosomes with ABA-spermine under mild irradiation conditions results in covalent and specific binding of spermine with ribosomal proteins (27) and various groups in rRNA (28).…”
Section: Aba-spermine Cross-linking In 23 S Rrna Interferes With Clinmentioning
confidence: 78%
“…Our results are discussed in view of NMR and crystallographic studies on the interactions of these drugs with the ribosome. 4 Cl) 70 S ribosomes and partially purified translation factors were prepared from E. coli K12 cells as described elsewhere (29). E. coli TA531 cells that lack chromosomal rrn alleles but contain wild-type or mutant pKK3535 plasmids expressing wild-type or mutated 23 S rRNA (U2609C or U754A), respectively, were kindly provided by Prof. A. S. Mankin (University of Illinois) and used as a source of ribosomes in studying the effect of certain mutations on the mechanism of drug binding to E. coli ribosomes.…”
mentioning
confidence: 99%